This is the equation right now, but (on the right side) I actually don't need the sum from mth=1,...,mth=mon but instead I need the sum from the mon where y was equal to 1 for the last time until mth=mon, if that makes sense. Is this possible?
Code: Select all
Variable x(mth); Scalar t(w); binary variable (y(w,mon)) set i,w,mon; alias (mon,mth); .... Ver(i,w,mon).. ord(i)*t(w)-1+(M*Y(w,mon)) =G= sum( mth$(ord(mth) le ord(mon)) ,x(mth))
So let's say we have
y(1)=0, y(2)=1, y(3)=0, y(4)=1, y(5)=0
I would need the following sum to be in the equation
.... =G= x(1)+x(2)
.... =G= x(3)+x(4)
.... =G= x(5)
Obviously the equations would change with the y(mon).
Thanks a lot in advance!